On the Comparison of Self-Perception, Emotional Self-Regulation, and Attachment Styles between Normal People and Drug-Dependent People - F Kari; O GhafariNouran; T Moosazade (Drug Control Headquarters, Research and Education Office, 2015)
The present study aims to compare self-perception, emotional self-regulation, and attachment styles between normal individuals and drug-dependent people. Method: The research method of this study was causal-comparative. All the addicts referring to the rehab center of Nir City (situated in Ardabil) constituted the statistical population of the study. Then, the number of 60 participants (two 30-person groups) was selected as the participants of the study via convenience sampling. For data collection purposes, self-perception scale, self-regulation scale, and adult attachment questionnaire were used. Results: The results showed that drug-dependent individuals received lower self-perception and self-regulation scores compared to normal individuals and received higher scores in insecure attachment styles than the normal participants. Conclusion: The results of the study suggest that low levels of self-perception and self-regulation along with insecure attachment styles are probably considered as risk factors for individuals' tendency to substance use.